Anthropometric and performance perspectives of female competitive surfing - Barlow, M. J.; Rowe, J.; Ruffle, O.; Davidson, M.; O`Hara, J. (Human Movement, 2016)
Purpose. To evaluate the anthropometric profiles of female surfers and to identify whether any anthropometrical factors might predict competitive ranking. Secondly, to evaluate the activity profile of female competitive surfing with respect to environmental conditions using Global Positioning System (GPS) derived measures.